Development of Reading Comprehension Teaching Materials Using Somatic Auditory Visual and Intellectual Models for Class IV of Primary Schools - Elvima Nofrianni; Syahniar Syahniar (Postgraduate School, Universitas Negeri Padang, 2019)
This study aims to describe the process of developing reading comprehension materials and producing reading comprehension teaching materials using the Somatic Auditory Visual And Intellectual model for teachers and students in grade IV of elementary schools that are valid, practical, and effective. This research is a development research based on the 4-D development model. The feasibility of teaching materials is obtained through the validation of the feasibility of content, language, presentation and graphics through expert validators and practitioner validators. The validation results from expert validators show that the teaching material reads the understanding using the Somatic Auditory Visual And Intellectual Model gets a percentage of 84.37%, this means the development of teaching materials carried out is in accordance with the feasibility of content, language, presentation, and graphics, so it can be said to be very valid . Meanwhile, practitioners' validators received 98.53% with a very valid category. Validity, practicality, and effectiveness tests are obtained through limited trials and broad dissemination stages so that teaching materials that are valid, practical, and effective are obtained, and are able to improve students' reading comprehension skills. It can be concluded that teaching reading comprehension materials using the Somatic Auditory Visual And Intellectual model developed can be used in reading comprehension learning in grade IV of elementary school.